2017
DOI: 10.1016/j.lungcan.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

The race to target MET exon 14 skipping alterations in non-small cell lung cancer: The Why, the How, the Who, the Unknown, and the Inevitable

Abstract: A number of small molecule tyrosine kinase inhibitors (TKIs) have now been approved for the treatment of non-small cell lung cancers (NSCLC), including those targeted against epidermal growth factor receptor, anaplastic lymphoma kinase, and ROS1. Despite a wealth of agents developed to target the receptor tyrosine kinase, MET, clinical outcomes have as yet been disappointing, leading to pessimism about the role of MET in the pathogenesis of NSCLC. However, in recent years, there has been a renewed interest in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 95 publications
(121 reference statements)
2
122
1
2
Order By: Relevance
“…Originally designed as a MET inhibitor, crizotinib distinguished itself in clinical trials via tumor reduction treatment in patients with anaplastic lymphoma kinase‐positive NSCLC , although more recent evidence suggests that crizotinib can benefit patients with the MET exon 14 skipping mutation, which occurs in 3%–4% of patients with lung adenocarcinoma and less frequently in other tumor types . Several other small‐molecule MET inhibitors are also under investigation for use as NSCLC treatments in patients with exon 14 skipping mutations . These largely disappointing data underscore the challenge of realizing the clinical utility of MET inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Originally designed as a MET inhibitor, crizotinib distinguished itself in clinical trials via tumor reduction treatment in patients with anaplastic lymphoma kinase‐positive NSCLC , although more recent evidence suggests that crizotinib can benefit patients with the MET exon 14 skipping mutation, which occurs in 3%–4% of patients with lung adenocarcinoma and less frequently in other tumor types . Several other small‐molecule MET inhibitors are also under investigation for use as NSCLC treatments in patients with exon 14 skipping mutations . These largely disappointing data underscore the challenge of realizing the clinical utility of MET inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…MET exon 14 skipping mutations, high-level MET amplification and BRAF and ROS1 mutations have all been identified as important driver events in NSCLC, occurring in 1-3% of lung cancers [76,82]. A study investigating the future science group www.futuremedicine.com OAK atezolizumab vs docetaxel [47,60] Checkmate 057 nivolumab vs docetaxel (non-squamous) [36] Keynote 010 pembrolizumab vs docetaxel (PD-L1+) [ effectiveness of ICIs in MET exon 14-mutated NSCLC patients concluded that, despite frequent PD-L1 expression, treatment responses were uncommon and lower than those observed with MET-targeted therapy [83].…”
Section: Other Mutational Markersmentioning
confidence: 99%
“…A review of multiple case reports describing responses to single agent MET TKI in patients harboring MET Δexon14 mutations revealed that co-existence of MET amplification is frequent (911,2931). Furthermore, when MET IHC is reported, it is uniformly high among responders.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these observations, clinical trials are now using MET copy number, Δexon14 MET alterations, and/or measurements of phosphorylated MET to enrich for patients likely to benefit from MET-directed therapies (11). There are multiple phase II trials using type I MET TKI.…”
Section: Introductionmentioning
confidence: 99%